Clinical analysis of 13 cases of primary squamous-cell thyroid carcinoma - Ou, Di; Ni, Chen; Yao, Jincao; Lai, Min; Chen, Chen; Zhang, Yajiao; Jiang, Tian; Qian, Tingting; Wang, Liping; Xu, Dong (Frontiers in Oncology, 2022)
Objective To analyze the clinical features, ultrasonographic manifestations, pathological features, treatment and prognosis of primary thyroid squamous cell carcinoma (PSCTC) and summarize the experience in diagnosis and treatment of this condition. Methods A retrospective analysis was conducted on patients who were admitted to Zhejiang Cancer Hospital from 2007 to 2021 due to thyroid nodules or thyroid malignant tumors that were ultimately confirmed by postoperative pathology as primary thyroid squamous cell carcinoma. We summarize the general situation, clinical information, laboratory examination, ultrasonic image characteristics, pathological examination, clinical treatment and prognosis of the patients. Results PSCTC is most often seen in older men and progresses rapidly. In laboratory tests, some patients had elevated levels of tumor markers (CA199, squamous cell carcinoma antigen level), thyroglobulin levels and tumor-related substances, but all these indicators lacked specificity. The ultrasound features of PSCTC are mainly hypoechoic, hard, substantial nodules with gross borders and a grade 1-2 blood flow signal, sometimes with signs of necrosis and calcification. In terms of treatment, PSCTC is mainly surgically resected, though some patients in this study underwent iodine-131 radiation therapy, local radiotherapy, and chemotherapy with unclear results. None of the patients survived for very long after treatment, but the prognosis of patients with highly differentiated squamous carcinoma was significantly better than that of patients with poorly differentiated squamous carcinoma. Papillary thyroid carcinoma may be one of the causes of PSCTC. Conclusion PSCTC is a malignant tumor with high malignancy and rapid clinical progression. Treatment options are mainly based on surgical resection and can be supplemented with radiotherapy and chemotherapy, but there is still a lack of a standardized treatment management system, and more cases and reports are needed to accumulate data.